THE IMPROVEMENT OF THE SPRING TAUS SLIPPERS - Melnychuk, V. O.; Mishchenko, A. A.; Savchuk, O. M. (Science and Transport Progress, 2009)
The TAUS slippers (a patent owner is the Transport Academy of Ukraine, the Eastern Center) [1] are developed for typical freight bogies of model 18-100 in order to increase up to 100…120 km/h the safe traffic speed of operation stock wagons. After a simple modernization during the depot repair of the wagon the slippers are to be reequipped into the elastic gapless TAUS ones. It allows increasing the critical wagon speed due to reducing the hunting vibrations of bogies. The paper is devoted to consideration of issues of further improvement of these slippers.